2020
DOI: 10.1177/2158244020939530
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Quality in Systematic Literature Reviews: A Study of Novice Rater Training

Abstract: This study investigated performance variability when graduate students critically appraised original studies from a systematic review. Fourteen doctoral students from different academic programs, with no systematic review experience, received training on the Methodological Quality Questionnaire (MQQ) rating scale. Participants were mostly male (71%) and non-native English speakers (79%). Each rater was randomly assigned one original study to independently assess using the MQQ. Their scores were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Previous researchers have used the Joanna Briggs Institute Methodological Quality Questionnaire (MQQ) framework (Acosta et al, 2020 ) to evaluate the methodological quality of the selected articles. This method quality checklist provides researchers with a basis for critical evaluation in terms of nine dimensions: theoretical definition, operational definition, research design, sample design, sample description, data credibility, data analysis, practical impact, and policy impact.…”
Section: Methodsmentioning
confidence: 99%
“…Previous researchers have used the Joanna Briggs Institute Methodological Quality Questionnaire (MQQ) framework (Acosta et al, 2020 ) to evaluate the methodological quality of the selected articles. This method quality checklist provides researchers with a basis for critical evaluation in terms of nine dimensions: theoretical definition, operational definition, research design, sample design, sample description, data credibility, data analysis, practical impact, and policy impact.…”
Section: Methodsmentioning
confidence: 99%
“…A quality assessment was also conducted on the extracted data. A series of quality assessment questions, based on the Methodological Quality Questionnaire [6], were answered to determine the extracted data's overall quality, The quality assessment questionnaire (see Appendix B) focused on assessing the source and author creditability, selection bias, methodological rigor, and usefulness in addressing the research question. Answers were graded as either "Yes", "No", "Can't Tell" or "Not Applicable", where factors to consider were listed under each criterion.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…The importance of communication and knowledge sharing in any project-based environment is essential for project success, and this has become more evident with the rise of digital project execution [3]. Additionally, the drive toward project virtual teams (VT) has accelerated with the widespread proliferation of new digital communication technologies and the global COVID-19 pandemic [4][5][6]. A survey suggested that approximately 66% of multinational corporations utilize VTs, where 80% of the respondents believed this number would continue to increase [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies generate adequate contributions to the field, whereas others produce biases. Therefore, the quality of the research methodology of the included articles was explicitly and systematically assessed, specifically in the stage of full-text screening, using a scoring instrument adapted from the Methodological Quality Questionnaire (Acosta et al, 2020). This reflected the quality of the evidence within each study and provided a general score of methodological quality.…”
Section: Quality Assessmentmentioning
confidence: 99%